Evaluation of three native entomopathogenic nematodes (Rhabditidae) against third instar larvae of Phyllophaga menetriesi (Coleoptera: Scarabaeidae) - Quintero Marín, M.P.; Caicedo, AM; Montoya Lerma, J.; Gaigl, A (Springer, 2006)
The infectivity and pathogenicity of three native entomopathogenic nematodes (Heterorhabditis (HNI 0100 and sp-CIAT) and Steinernema (SNI 0198)) were evaluated in third instar larvae of Phyllophaga menetriesi (Blanchard) under laboratory conditions. Concentrations of 7000 and 13,000 infective juveniles per millilitre were applied to the coleopteran larval host (individuals) that had been placed in plastic cups with 40 g of sterile sand at 5.8% (w/w) moisture. The evaluations were done 5 and 10 days after treatment. It was observed that both the percentage of infectivity (74.5%, n = 247), measured in terms of percentage of penetration and the percentage of pathogenicity (10.5%, n = 247) of the three native nematodes were significantly different due to the treatments. Steinernema had the highest values of infectivity (>80%), but no pathogenicity. In contrast, the treatments with Heterorhabditis, despite having the lowest degree of infectivity (52.9%), had the highest mortality values (31.6%). Therefore, the Heterorhabditis strains were considered to be the most promising as biological control organisms within an integrated pest management programme due to their higher degree of pathogenicity. Nevertheless, different strains and species of native nematodes should be evaluated in all the developmental stages of the pest.